Selective Metallization of Polymers: Surface Activation of Polybutylene Terephthalate (PBT) Assisted by Picosecond Laser Pulses. Issue 4 (23rd November 2021) - Camargo, Magali K.; Uebel, Martin; Kurniawan, Mario; Ziegler, Karl F.; Seiler, Michael; Grieseler, Rolf; Schmidt, Udo; Barz, Andrea; Bliedtner, Jens; Bund, Andreas
Abstract : The selective metallization of nonconductive polymer materials has broad applications in the fields of integrated circuit technology and metallized patterns. This work discusses a methodology to pattern metal tracks on polybutylene terephthalate substrates. The process consists of three steps: 1) surface patterning with picosecond laser pulses (1030 nm) in air, 2) Pd seeding via treatment in PdCl2 solution, and 3) selective metallization via electroless copper deposition. Picosecond laser irradiation promotes not only surface roughening but also chemical modification to enable Pd seeding as the polymer surface acquires the ability to reduce Pd(II)‐chloride species to metallic Pd. The laser parameters, as well as the PdCl2 concentration and seeding temperature, have an influence on the polymer surface morphology, the concentration and distribution of metallic Pd, and the copper layer properties. Homogeneous copper layers with well‐defined geometries, good coating‐substrate adhesion, and high electrical conductivity can be obtained. This is ascribed to the synergistic effect of the chemical surface activation and roughness development (from 0.13 to ≈1.6 μm). As the patterning and surface activation are performed in air, directly on the as‐received polymer substrate, this methodology shows great potential for metallization of electronic devices with 3D complex geometries. Abstract : A simple methodology is developed to selectively metallize commercial catalyst‐free polybutylene terephthalate (PBT) substrates. Picosecond laser pulses are applied to modify the PBT surface in air. The ablated surface undergoes chemical modification and can act as reducing agent to promote Pd‐seeding in a subsequent step. The metallization proceeds via electroless copper plating producing layers with good adhesion and electrical conductivity.